1997
DOI: 10.1046/j.1365-2648.1997.1997025006.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators in clinical nursing: a review of the literature

Abstract: The purpose of the present study was, by means of a literature review, to describe and analyse the characteristics of clinical indicators used to assess and promote quality improvement in nursing care. It was found that a generally accepted definition of a clinical indicator is a 'quantitative measure that can be used as a guide to monitor and evaluate the quality of important patient care and support service activities'. By the seriousness of the event and the degree to which it can be avoided, clinical indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 66 publications
2
64
0
7
Order By: Relevance
“…The data analysis showed that 44% of the subjects When the occurrence of PUI and falls in the hospital studied were analyzed, it was found that these indicators were considered by 100% of the nurses as highly relevant to evaluate the quality of the nursing care, corroborating the literature (15)(16) . Other indicators considered by the nurses as highly relevant or relevant for the qualification of the care are intimately related to the daily nursing tasks, such as incidence of phlebitis, accidental extubation and incidence of non-compliance in the medication administration.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The data analysis showed that 44% of the subjects When the occurrence of PUI and falls in the hospital studied were analyzed, it was found that these indicators were considered by 100% of the nurses as highly relevant to evaluate the quality of the nursing care, corroborating the literature (15)(16) . Other indicators considered by the nurses as highly relevant or relevant for the qualification of the care are intimately related to the daily nursing tasks, such as incidence of phlebitis, accidental extubation and incidence of non-compliance in the medication administration.…”
Section: Discussionsupporting
confidence: 60%
“…It is noteworthy that the rate of work accidents was also considered, by 100% of the sample, as a qualifier of the care by the nurses. This indicator may evidence structural or procedural failures of the care, as shown by the study (15) that encountered rates of 72% of concordance of the Gabriel CS, Melo MRAC, Rocha FLR, Bernardes A, Miguelaci T, Silva MLP.…”
Section: Discussionmentioning
confidence: 92%
“…The concept arose from the quality improvement agenda of the Joint Commission on Accreditation of Health Care Organizations (JCAHO) in the United States (US) in the late 1980s [3]. More recently, concerns about the changing nurse skill mix have led researchers to investigate associations between the incidence of nursing-sensitive outcomes and levels of nurse staffing [4-8].…”
Section: Introductionmentioning
confidence: 99%
“…The determination of care aspects to be measured was founded on the recommendation of high frequency problems that affect a great number of patients, thus establishing a risk situation (6) . Problems related to ethical and legal aspects of care documentation were also taken into account, as well as those problems liable to being minimized or solved with permanent and continuous education measures (6,14) .…”
Section: Methodsmentioning
confidence: 99%
“…Indicators signal discrepancies toward the determined desired standard, and act as an alert that identifies and draws attention to the necessary review of key care elements (6) .…”
Section: Introductionmentioning
confidence: 99%